2022
DOI: 10.1002/jcc.27050
|View full text |Cite
|
Sign up to set email alerts
|

Large scale peptide screening against main protease of SARS CoV‐2

Abstract: The COVID‐19 pandemic has been a public health emergency, with deadly forms constantly emerging around the world, highlighting the dire need for highly effective antiviral therapeutics. Peptide therapeutics show significant potential for this viral disease due to their efficiency, safety, and specificity. Here, two thousand seven hundred eight antibacterial peptides were screened computationally targeting the Main protease (Mpro) of SARS CoV‐2. Six top‐ranked peptides according to their binding scores, binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…As Aβs are quite aggregative and cause Alzheimer's-type dementia, BACE1 has been a target enzyme to develop drugs against Alzheimer's disease. Screening a library of substrates to find superior cleavage sequences is quite useful for future drug development [15][16][17]. The digestion of the P 3 library suggested that the Ser(Me) residue is a candidate for future drug design.…”
Section: Discussionmentioning
confidence: 99%
“…As Aβs are quite aggregative and cause Alzheimer's-type dementia, BACE1 has been a target enzyme to develop drugs against Alzheimer's disease. Screening a library of substrates to find superior cleavage sequences is quite useful for future drug development [15][16][17]. The digestion of the P 3 library suggested that the Ser(Me) residue is a candidate for future drug design.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, peptidyl inhibitors N3 and D-4-77 inhibit M pro , showing half-maximal inhibitory concentrations (IC 50 ) of 125 and 0.95 μM, respectively. Furthermore, bioactive peptides from natural sources that offer efficacy and safety as the potential SARS-CoV-2 M pro have been urgently needed …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bioactive peptides from natural sources that offer efficacy and safety as the potential SARS-CoV-2 M pro have been urgently needed. 29 Bioactive peptides are typically small dietary protein fragments consisting of 2−20 amino acid residues with an average molecular weight of <3 kDa. 30 They are characterized by various physiological activities, such as antioxidative, 31,32 antihypertensive, 33,34 antidiabetic, 35 antimicrobial, 36 and immunomodulatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al designed 229E-HR2P, a peptide for HR1 and HR2 regions of the HCoV-229E that could be utilized as an antiviral drug when accompanied by different antiviral drugs to exert a synergistic effect [30]. From several other studies, it has been demonstrated that several AMPs can also act against a broad range of viruses, referred to as AVPs [31][32][33][34][35][36][37][38]. Several patents of peptides as drug candidates against SARS and MERS are already available, and it is worth noting that peptide inhibitors have the benefits of higher tissue penetration, cost-effectiveness, specificity, and minimal toxicity [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The success of this molecule has reinvigorated the investigation for novel protease inhibitors based on peptides and peptidomimetics [47]. Several computational studies also revealed that AVPs may be further developed to inhibit the Mpro of SARS-CoV-2 [37,48]. Virtual screening of a combinatorial peptide library was also conducted against the active sites of Mpro and receptorbinding domain (RBD) [49].…”
Section: Introductionmentioning
confidence: 99%